The Correlation of CEO Power, Gender and Product Market Competition on Firm Value in the Property and Real Estate Sector - Pangesti, Eka Ningtyas; Mustikowati, Rita Indah; Asna, Asna; Firdaus, Riril Mardiana (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This study aims to analyse the relationship between Chief Executive Officer (CEO) Power, gender, Product Market Competition on firm value. The research design was quantitative method with an associative approach. The population were property and real estate sector companies listed on the Indonesia Stock Exchange from 2019 to 2022, total of 144 sample data from 36 companies. The dependent variable is firm value, the independent variables are CEO power, gender and product market competition. Chief Executive Officer (CEO) power is measured by the parameters of age, education level and share ownership. Firm value is measured using Tobins'Q. Analysis of the level of competition used the industry-adjusted price-cost margin (IPCM) approach. The analysis technique used is Spearman correlation. The results showed that there was no significant relationship between CEO power: age and share ownership, as well as CEO gender on firm value, while there was a significant relationship between CEO power: education level and product market competition on firm value.